Penerapan Sanksi Hukum Pidana Bagi Pelaku Geng Motor Yang Meresahkan Masyarakat - Jon Antoni (Albayan Journal of Islam and Muslim Societies, 2024)
The phenomenon of motorcycle gangs has become a growing social concern, particularly in urban areas such as the city of Medan. These gangs are often involved in various criminal acts, including assault, vandalism of public facilities, and illegal street racing, all of which disturb public order. This study aims to examine the application of criminal sanctions against motorcycle gang members who cause public unrest. The research employs a normative juridical approach by analyzing relevant laws and regulations, complemented by empirical research through interviews with police officers, community members, and victims of motorcycle gang actions. The collected data is analyzed using qualitative analysis techniques. The findings reveal that the police play a crucial role in addressing motorcycle gang activities through preventive measures such as routine patrols and community outreach programs, as well as enforcing the law against perpetrators involved in criminal acts. The common crimes committed by motorcycle gangs include assault, murder, theft, property damage, and traffic violations. The legal sanctions imposed on perpetrators are in accordance with the Indonesian Penal Code (KUHP) and the Law on Traffic and Road Transportation, consisting of imprisonment, fines, and administrative penalties. The conclusion of this study is that law enforcement efforts against motorcycle gangs are in line with existing regulations. However, challenges remain, particularly in terms of evidence collection and handling perpetrators, many of whom are underage. Therefore, greater community involvement and collaboration between law enforcement agencies, the government, and educational institutions are recommended to comprehensively address the issue of motorcycle gangs.